Plasma cyclic 3′,5′-adenosine monophosphate in patients with elevated pulmonary pressure due to left-to-right shunt - Loukanov, Tsvetomir; Takahashi, Hiroaki; Tonchev, Pencho; Gross, Jasmin; Bettendorf, Markus; Gorenflo, Matthias (The Canadian journal of cardiology, 2011)
Background - Increased pulmonary blood flow in patients with left-to-right shunt has been shown to be associated with alterations in prostacyclin-synthesis. There are limited data with respect to the plasma cAMP in patients with elevated pulmonary artery pressure due to left-to-right shunt. We hypothesized that plasma cAMP might be influenced by pulmonary blood flow or pressure in patients with left-to-right shunt. - Methods - Plasma cAMP from venous blood was measured in 122 healthy controls aged 8.3 (0.2 - 14.9) years (median [range]) and in 130 patients with left-to-right shunt aged 1.4 (0.1 - 19.1) years by radioimmunoassay. - Results - Plasma cAMP in controls and in patients was similar and decreased with age. Healthy infants (n = 42) showed higher plasma cAMP (46 [27-112] nmol/l) than children > 6 years of age (n = 40, 39 [19-73] nmol/l; P < 0.001). - Conclusions - These values should be taken into consideration when reporting plasma values for cAMP in patients with congenital heart disease. The values for healthy children obtained in this study should allow a better interpretation of plasma cAMP levels in various disease conditions such as chronic renal failure, liver chirrhosis, hyperthyreosis, or children with intellectual disability. - Résumé - Introduction - Une augmentation du débit sanguin pulmonaire chez les patients avec un shunt gauche-droit s'est révélée associée aux altérations de la synthèse de la prostacycline. Il y a peu de données à l'égard de l'AMPc plasmatique chez les patients avec une pression artérielle pulmonaire élevée due à un shunt gauche-droit. Nous avons fait l'hypothèse que l'AMPc plasmatique puisse être influencé par la pression ou le débit sanguin pulmonaire chez les patients avec un shunt gauche-droit. - Méthodes - L'AMPc plasmatique du sang veineux a été mesurée chez 122 témoins en santé âgés de 8,3 (0,2 - 14,9) ans (médiane [étendue]) et chez 130 patients avec un shunt gauche-droit âgés de 1,4 (0,1 - 19,1) ans par un radio-immunoessais. - Résultats - L'AMPc plasmatique des témoins et des patients était similaire et diminuait avec l'âge. Les nourrissons en santé (n = 42) montraient une AMPc plasmatique plus élevée (46 [27-112] nmol/l) que les enfants > 6 ans (n = 40, 39 [19-73] nmol/l; P < 0,001). - Conclusions - Ces valeurs devraient être prises en considération lorsqu'on rapporte les valeurs plasmatiques de l'AMPc chez les patients avec une maladie cardiaque congénitale. Les valeurs obtenues chez les enfants en santé de cette étude devraient permettre une meilleure interprétation des niveaux d'AMPc plasmatique dans différentes conditions médicales comme l'insuffisance rénale chronique, la cirrhose hépatique, l'hyperthyroïdie ou chez les enfants avec une déficience mentale.
Gesehen am 08.11.2022